Hemodialysis‐induced regional left ventricular systolic dysfunction. Issue 4 (17th June 2016) - Nie, Yuxin; Zhang, Zhen; Zou, Jianzhou; Liang, Yixiu; Cao, Xuesen; Liu, Zhonghua; Shen, Bo; Chen, Xiaohong; Ding, Xiaoqiang
Abstract: Introduction Hemodialysis (HD) patients are under observably elevated cardiovascular mortality. Cardiac dysfunction is closely related to death caused by cardiovascular diseases (CVD). In the general population, repetitive myocardial ischemia induced left ventricular (LV) dysfunction may progress to irreversible loss of contraction step by step, and finally lead to cardiac death. In HD patients, to remove water and solute accumulated from 48 or 72 hours of interdialysis period in a 4‐hour HD session will induce myocardial ischemia. In this study, we evaluated the prevalence and potential risk factors associated with HD‐induced LV systolic dysfunction and provide some evidences for clinical strategies. Methods We recruited 31 standard HD patients for this study from Fudan University Zhongshan hospital. Echocardiography was performed predialysis, at peak stress during HD (15 minutes prior to the end of dialysis), and 30 minutes after HD. Auto functional imaging (AFI) was used to assess the incidence and persistence of HD‐induced regional wall motion abnormalities (RWMAs). Blood samples were drawn to measure biochemical variables. Findings Among totally 527 segments of 31 patients, 93.54% (29/31) patients and 51.40% (276/527) segments were diagnosed as RWMAs. Higher cTnT (0.060 ± 0.030 vs. 0.048 ± 0.015 ng/mL, P = 0.023), phosphate (2.07 ± 0.50 vs. 1.49 ± 0.96 mmol/L, P = 0.001), UFR (11.00 ± 3.89 vs. 8.30 ± 2.66 mL/Kg/h, P = 0.039) and lower albumin (37.83 ± 4.48 vs. 38.38 ± 2.53 g/L, P = 0.050) were found in patients with severe RWMAs (RWMAs in more than 50% segments). After univariate and multivariate analysis, interdialytic weight gain (IDWG) was found as independent risk factor of severe RWMAs (OR = 1.047, 95%CI 1.155–4.732, P = 0.038). Discussion LV systolic dysfunction induced by HD is prevalent in conventional HD patients and should be paid attention to. Patients would benefit from better weight control during interdialytic period to reduce ultrafiltration rate.